Ty claims the expressions x + x + 3 and 3x are equivalent. substitute 1 for x in the expressions see if ty is correct. x + x + 3 = 3x = are the expressions equivalent, yes or no?

Skip to content# Ty claims the expressions x + x + 3 and 3x are equivalent. substitute 1 for x in the expressions see

##
This Post Has 10 Comments

### Leave a Reply

Ty claims the expressions x + x + 3 and 3x are equivalent. substitute 1 for x in the expressions see if ty is correct. x + x + 3 = 3x = are the expressions equivalent, yes or no?

1) not equivalent

2) equivalent

3(a-b) and 3a-3b. Equivalent

2a(2+b) and 4ab. Not equivalent

3.The value of the second expression is 8, so the expressions are not equivalent.

Step-by-step explanation:

x+x+6

Let x=2

2+2+6 = 10

4+3x-2

Let x=2

4+3(2) -2

4+6-2 =8

The first expression is 10 and the second expression is 8, so the two expressions are not equivalent at x=2

3(a + b) and 3a + b - NOT EQUIVALENT because

3(a + b) = 3a + 3b

used distributive property a(b + c) = ab + ac

4(x + 2y) and 8y + 4x - EQUIVALENT because

4(x + 2y) = (4)(x) + (4)(2y) = 4x + 8y = 8y + 4x

used distributive property a(b + c) = ab + ac

and commutative property a + b = b + a

8x(4+z) and 32x+8z, = Not equivalent

9(g+h) and 9g+9h = Equivalent

no, those expressions are not equivalent, since they have different value for x other than 3, the problem take example x=1

3(a+b) is not equal to 3a+b

4(x+2y) is equal to 4x+8y

Step-by-step explanation:

3(a+b)

Distribute

3a+3b

This is not equal to 3a +b

4(x+2y)

Distribute

4x+8y

This is equal to 4x+8y

c. ;

2^4 * 5 should be it.

8x(4+z) and 32x+8z are not equivalent expressions.

9(g+h) and 9g+9h are equivalent expressions.

Step-by-step explanation:

8x(4+z) and 32x+8z

8x(4+z) , distribute 8x inside the parenthesis

8x times 4= 32x

8x times z= 8xz

8x(4+z) = 32x+8xz

8x(4+z) and 32x+8z are not equivalent expressions.

9(g+h) and 9g+9h

9(g+h), distribute 9 inside the parenthesis

9 times g is 9g and 9 times h is 9h

So 9(g+h)= 9g+ 9h

9(g+h) and 9g+9h are equivalent expressions.